A Winepress at Apollonia-Arsuf: More Evidence on the Samaritan Presence in Roman-Byzantine Southern Sharon - Tal, Oren (Liber Annuus, 2009)
Abstract This article examines the results of the 2006 and 2009 seasons in the far northern end of the site - a large mosaic floor winepress with a Greek inscription in the center of its treading floor. The inscription reads: “One God only, help / Cassianos together with (his) wife / and children and everyone.” Such commemorative inscriptions are mostly known from Samaritan cult buildings (synagogues). Both the inscription and the finds discovered in the area point to a Samaritan ownership over the complex in Byzantine times (ca. fifth-sixth centuries CE). The winepress is thus analyzed against its inscription and other Byzantine winepresses with inscriptions found in Palestine. Based on the archaeological evidence the winepress ceased to function in the first half of the sixth century CE (possibly in relation to the Samaritan revolt [529 CE]).